A theory of Catholic education - Whittle, Sean (Bloomsbury Publishing, 2015)
Presenting a robust and philosophically based account of education from the Catholic point of view, Sean Whittle engages with important debates and questions concerning the nature and purpose of Catholic education and schooling. The book opens with a review of the criticisms that have emerged about the prevalence of Catholic schools within the state system and, indeed, about the very notion of there being such a thing as ''Catholic education''. The author then goes on to survey official Church teaching on education and the work of key Catholic thinkers, Newman and Maritain, before moving on to.